STUDI KELAYAKAN INVESTASI PEMBANGUNAN APARTEMEN MAHASISWA DI KECAMATAN SUKARAME KOTA BANDAR LAMPUNG - Antusias Nurzukhrufa; Andi Asrul Sani; Thalitha Nurjannah (Universitas Kristen Maranatha, 2022)
The development of the Institut Teknologi Sumatera (ITERA) is growing rapidly along with the number of students which has an impact on the demand for student housing needs. The proliferation of housing with the target market of students around ITERA is unavoidable. However, until now, no developer or investor has seen this investment opportunity to build rental housing with apartment concepts around ITERA. Sukarame District is one of the sub-districts in Bandar Lampung City which is located directly adjacent to ITERA. The location is strategic because it has close access to the toll gate, is traversed by the Ryacudu road which connects the toll gate to the city center, and is directed as an educational and residential area. This study aims to determine the investment feasibility of building student apartments in Sukarame District, Bandar Lampung City. The method used to analyze investment feasibility is Capital Budgeting with 3 criteria, namely Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). The result is an NPV value of Rp. 387,851,947,410 which can be said to be feasible, with an IRR of 67%, greater than the discount rate of 4.26% so it can be said that it is feasible and PP with an investment period of 10 years has a payback period of 3.9 years which can be used. said to be worthy. From the results of the analysis of NPV, IRR, and PP, it can be concluded that the investment in the construction of student apartments in Sukarame District, Bandar Lampung City can be said to be feasible.